2016
DOI: 10.1007/s00281-016-0580-2
|View full text |Cite
|
Sign up to set email alerts
|

Influenza pathogenicity during pregnancy in women and animal models

Abstract: Pregnant women are at the highest risk to develop severe and even fatal influenza. The high vulnerability of women against influenza A virus infections during pregnancy was repeatedly highlighted during influenza pandemics including the pandemic of this century. In 2009, mortality rates were particularly high among otherwise healthy pregnant women. However, our current understanding of the molecular mechanisms involved in severe disease development during pregnancy is still very limited. In this review, we sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 66 publications
2
18
0
Order By: Relevance
“…The enhanced morbidity and mortality seen in pregnant women infected with the swine origin 2009 pandemic influenza virus triggered investigations into the underlying mechanisms of increased risk. Reports indicate increased mortality in pregnant mice and their offspring exposed to A/California/07/2009, enhanced lung immunopathology, and dysregulated progesterone and estrogen expression (13,36,68). In this study we confirm that infection of pregnant mice at mid-gestation with the pandemic H1N1 virus enhances maternal morbidity, and increases pre-term labor, incidence of SGA offspring and stillbirth, recapitulating clinical observations in pregnant populations.…”
Section: Discussionsupporting
confidence: 83%
“…The enhanced morbidity and mortality seen in pregnant women infected with the swine origin 2009 pandemic influenza virus triggered investigations into the underlying mechanisms of increased risk. Reports indicate increased mortality in pregnant mice and their offspring exposed to A/California/07/2009, enhanced lung immunopathology, and dysregulated progesterone and estrogen expression (13,36,68). In this study we confirm that infection of pregnant mice at mid-gestation with the pandemic H1N1 virus enhances maternal morbidity, and increases pre-term labor, incidence of SGA offspring and stillbirth, recapitulating clinical observations in pregnant populations.…”
Section: Discussionsupporting
confidence: 83%
“…It has also been observed that malnourished, diabetic, young children and elderly individuals exhibit increased morbidity and mortality from influenza virus infections. Conversely, these populations also have reduced vaccine responses compared to healthy adults [ 197 , 209 , 210 , 211 , 212 ]. To better meet the needs of these vulnerable populations, vaccines need to be optimized by either increasing antigen doses, adding adjuvants or implementing prime-boost strategies.…”
Section: Pre-clinical Animal Models Of High-risk Populationsmentioning
confidence: 99%
“…One study reported that vitamin supplements given at the time of vaccination improved vaccine responses in deficient mice [ 215 ]. Mice can also be used to examine other human conditions such as infancy [ 216 ], malnutrition [ 215 , 217 , 218 , 219 , 220 , 221 ], aging [ 197 , 222 , 223 , 224 ], diet-induced obesity [ 103 , 219 , 225 , 226 ] or pregnancy [ 205 , 212 , 227 , 228 , 229 , 230 , 231 , 232 , 233 ]. The variety of populations that the mouse model can mimic allows for vaccines to be evaluated for multitude of individuals.…”
Section: Pre-clinical Animal Models Of High-risk Populationsmentioning
confidence: 99%
“…Strikingly, pregnant women account for only 1% of the general population, yet experience an excessive rate of mortality of 5% on influenza virus infection (Centers for Disease Control and Prevention 2010). Interactions between hormones and immune mediators in systemic circulation and at the mother-fetal interface alter influenza pathogenesis in the pregnant host, as well as contribute to sex-based differences in the response to infection (Irving et al 2000;Raj et al 2014;van Riel et al 2016;Littauer and Skountzou 2018). Other comorbidities, including stress, depression, body mass index, aging, puberty, and exercise state, contribute to poor infection responses and can compound morbidity in pregnant hosts (Christian et al 2010;Avitsur et al 2011;Soydinc et al 2012;Christian 2014;Ingersoll 2017;Vom Steeg and Klein 2017).…”
Section: Pregnancymentioning
confidence: 99%
“…Pregnant mouse models, including syngenic mating between like strains of mice and allogenic mating between different strains of mice, yield insights into the altered influenza pathogenesis in pregnant hosts. Reduced viral clearance and eightfold higher viral titers characterize the lungs of syngeneic and allogenic pregnant mice infected during mid-gestation, with allogenic-mated mice showing more severe disease caused by fetal tolerance (van Riel et al 2016;Engels et al 2017;Littauer et al 2017). Increased disease severity is not strain-specific; increased viral loads are observed with influenza B-infected pregnant mice as well (Kim et al 2014).…”
Section: Pregnancymentioning
confidence: 99%